2021
DOI: 10.3390/genes12081109
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Phylogenetic Relationships and Genetic Variation among Rare, Phenotypically Similar Donkey Breeds

Abstract: The mitochondrial DNA (mtDNA) D-loop of endangered and critically endangered breeds has been studied to identify maternal lineages, characterize genetic inheritance, reconstruct phylogenetic relations among breeds, and develop biodiversity conservation and breeding programs. The aim of the study was to determine the variability remaining and the phylogenetic relationship of Martina Franca (MF, with total population of 160 females and 36 males), Ragusano (RG, 344 females and 30 males), Pantesco (PT, 47 females … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Phylogenetic analysis based on mtDNA classified two Croatian donkey breeds into the group Equus asinus africanus. Moreover, in other studies concerning the mtDNA D-loop, the donkey breeds included in the study are also in the phylogenetic group Equus asinus africanus, which was established by other authors [25,28,29,31]. All identified haplogroups of the Istrian donkey population (A, B), and one of the Littoral-Dinaric donkey population (D), are close to the Italian donkey breeds, which is important for understanding the breed's phylogenetic position and further breeding consolidation.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Phylogenetic analysis based on mtDNA classified two Croatian donkey breeds into the group Equus asinus africanus. Moreover, in other studies concerning the mtDNA D-loop, the donkey breeds included in the study are also in the phylogenetic group Equus asinus africanus, which was established by other authors [25,28,29,31]. All identified haplogroups of the Istrian donkey population (A, B), and one of the Littoral-Dinaric donkey population (D), are close to the Italian donkey breeds, which is important for understanding the breed's phylogenetic position and further breeding consolidation.…”
Section: Discussionmentioning
confidence: 88%
“…MtDNA contains a non-coding control region, also called the displacement-loop region (Dloop) [23]. Previous studies of donkey mtDNA D-loop (control region) sequences depicted the genetic relationships and origin of worldwide modern donkey breeds well [19,[24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…However, donkey's phylogeny has not been properly recorded. In a study conducted by Mazzatenta et al (2021) D-loop of critically endangered breeds of Italian donkeys, Martina Franca, Ragusano, Pantesco and Catalonian has been evaluated. For a sample set of 77 individual DNA, 56 haplotypes were identified.…”
Section: Resultsmentioning
confidence: 99%
“…The evolutionary studies on equines suggested prominent information on their origin, evolution and domestication (Renaud et al, 2018) but the data regarding donkeys have not been documented properly since there is a theory circulating that donkeys are believed to be domesticated twice (Schubert et al,2014;Librado et al, 2017;Rossel et al, 2008;Beja Pereira et al,2004). In India, scanty reports are available about characterization of equine germplasm (Gupta et al, 2012;2015;Pal et al, Mitochondrial DNA Variation and Genetic Relationships in Indian Halari Donkey Breed using D-Loop Region 2013, 2021 and it needs to be explored in depth. Few reports are also available on Halari donkey milk (Bhardwaj et al, 2019;.…”
Section: Introductionmentioning
confidence: 99%
“…Semen as well as blood samples were collected from a population of twenty-six healthy male donkeys (Martina Franca), with age between 2 and 19 years. The Martina Franca donkey (MF) has been considered to be an endangered breed since the early 1980s [22,23], and its population consists of less than 200 females and 40 males [24].…”
Section: Inclusion Criteria and Sample Collectionmentioning
confidence: 99%